2017
DOI: 10.1016/j.aott.2016.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Chemotherapy in primary osteogenic sarcoma in patients over the age of forty

Abstract: ObjectiveIn this study, we sought to review the clinical and histopathological features and the chemotherapy regimens in osteogenic sarcoma in patients over 40 years of age, and we aimed at identifying the possible prognostic factors in this particular group of patients.MethodsWe reviewed 287 patients with osteosarcoma treated between the year 1986 and 2010. Patients from this group who met the following criteria were considered eligible for our study; presence of primary OS, had typical histological and radio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 23 publications
1
8
0
Order By: Relevance
“…In contrast, a recent paper poses doubts on the need to administer chemotherapy to these patients (12). Some retrospective studies including osteosarcoma patients over 40 treated with chemotherapy have reported data showing a probability of survival similar to those achieved in younger patients (8,11).…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…In contrast, a recent paper poses doubts on the need to administer chemotherapy to these patients (12). Some retrospective studies including osteosarcoma patients over 40 treated with chemotherapy have reported data showing a probability of survival similar to those achieved in younger patients (8,11).…”
Section: Discussionmentioning
confidence: 92%
“…Some retrospective studies including osteosarcoma patients over 40 treated with chemotherapy have reported survival probabilities similar to those achieved in younger patients (8,11). A retrospective EMSOS study (10) observed an advantage in terms of prognosis for those patients who received chemotherapy above those who did not; however, it did not provide details of the chemotherapy protocols used.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They found that tumor site, metastasis at diagnosis, surgery, and surgical margins were significantly associated with survival, whereas chemotherapy had no influence on survival. However, some studies reported that aggressive treatment with chemotherapy can offer a favorable outcome for older osteosarcoma patients 11-13. Although osteosarcoma is radioresistant, some studies have reported that radiotherapy is an effect adjuvant treatment for local control 14, 15.…”
Section: Introductionmentioning
confidence: 99%
“…The even lower incidence of BS results in a paucity of data, which mainly derives from retrospective case series on osteosarcoma patients, confirming a worst prognosis in the adult population [29][30][31][32]. The distinct negative clinical features reported were the longer time from symptoms onset to diagnosis, a more advanced stage ab initio, primary location (more truncal tumors) in addition to specific treatments that are less aggressive, beside exclusion from clinical trials.…”
Section: Wide R0 Surgerymentioning
confidence: 99%